Associative enterprises, Recuperated Companies and the Social Economy in Argentina - Deux Marzi, María Victoria; Vázquez, Gonzalo (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2009)
Towards the end of the twentieth century, Argentina faced a social, political and economic crisis of monumental dimensions. This emergency translated into increased poverty and inequality, and a structural crisis in the job market. In this context, a number of strategies arose, aimed at recuperating some of the loss, and generating new possibilities in the job market. Some of these strategies were identified as part of a wide-ranging and heterogeneous series of experiments in social economics. This work will focus on an analysis of 611 associate market initiatives and 50 recuperated companies in Argentina, for the purpose of characterizing these experiences and showing their drive to create and regenerate sources of employment. To achieve this, we will take as our starting point the data collected for the Study “Socio- Economic Associative Initiatives: Vulnerability and Sustainability” (ICO-UNGS, 2006).